Digging activity of the common mole under the conditions of Belarus and the need for its scaring - Gorovykh, Olga; Dubnovitsky, Yuri; Saevich, Konstantin (Journal of the Belarusian State University. Ecology, 2023)
The article presents the data of hunting for the mole in the republic in the last century, during the period when the hunting for the mole was carried out, the factors contributing to the increase in the number of the mole population at the present time are indicated: the absence of natural enemies, the adequacy of the food supply throughout the year, the lack of industrial catching. New data on the average size of molehills are given: diameter Dcr = 28 ± 2 cm, height Hcr = 9.7 ± 0.6 cm and their number in the studied areas of the Pruzhany region. Based on the data of counting molehills in Dzerzhinsky, Stolbtsovsky, Uzdensky, Pruzhany and Pinsk districts in areas under natural grasses or sown with cereal crops, an average number of molehills in the Brest region was established, which amounted to 36 molehills (average area 2.2 m2) per plot 10×10 m2, which is about 2 % of the total area. An approximate area was determined, amounting to 21.5 thousand hectares, located under molehills in the Brest region. The influence of the mole on the amount of processed land and the humus formation associated with this, depending on the intensity of catching, is considered; this year, this value amounted to 15.202 million tons of soil. The need to scare away moles, at least from areas of intensive visitation by people and domestic animals (garden plots) was noted due to the high infection of moles with ectoparasites dangerous to humans and animals. Information is provided on a new mole repeller developed in Belarus and mastered for production, based on calcium sulfate dihydrate, which does not contain pesticides and does not lead to the death of animals, but helps to leave the territory treated with this mole repeller.
Keywords: common mole; wormholes; damage; earthworms